2017
DOI: 10.1007/s10802-016-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Pow! Boom! Kablam! Effects of Viewing Superhero Programs on Aggressive, Prosocial, and Defending Behaviors in Preschool Children

Abstract: Many schools and parents try to motivate children to become defenders of victimized peers. Defending behavior is common in the media (particularly in superhero programs); however, no study has examined the effect of media on defending behavior. The aim of the study was to examine longitudinal associations between superhero engagement and a variety of aggressive, prosocial, and defending behaviors in preschool children. Participants consisted of 240 preschoolers (49% male) and their parents who reported on chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 58 publications
1
22
1
2
Order By: Relevance
“…Therefore, children may interpret the behavior of a superhero to be acceptable, even when they are committing severely violent acts, such as "use of a lethal weapon", "murder", and "mass murder". This relationship between violence depicted in the media and more frequent aggressive behavior has been found in several published studies [3,[18][19][20]. Furthermore, McCrary suggested that television superheroes may influence the development of moral values in kindergarten-aged children, and Martin found that the feelings children have towards superheroes are related to the way in which they feel about themselves [21][22].…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, children may interpret the behavior of a superhero to be acceptable, even when they are committing severely violent acts, such as "use of a lethal weapon", "murder", and "mass murder". This relationship between violence depicted in the media and more frequent aggressive behavior has been found in several published studies [3,[18][19][20]. Furthermore, McCrary suggested that television superheroes may influence the development of moral values in kindergarten-aged children, and Martin found that the feelings children have towards superheroes are related to the way in which they feel about themselves [21][22].…”
Section: Discussionmentioning
confidence: 64%
“…For example, recent research suggests that children struggle in understanding popular media models of defending behavior. In particular, Coyne and colleagues () investigated whether preschoolers would be more likely to engage in defending behavior if they had exposure to superheroes, who frequently act very aggressively in their bid to defend others against harm. Unfortunately, children with greater superhero engagement were not more likely to engage in defending behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These children who are willing to actively defend others against bullying are referred to as defenders (Olweus, ). Defenders are seen in all types of bullying behavior, including physical, verbal, relational, and cyberbullying (e.g., Chen, Cheng, & Ho, ; Coyne et al, ; Pečjak & Pirc, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet we cannot assume that increased exposure always has a positive impact upon how children perceive their own and other nations (Barrett, 2012), as this depends on what content children consume. Thirdly, we must continue questioning the suitability and impact of media upon children, highlighting unintended or unimagined consequences of media exposure, as Coyne et al (2017) did through their findings that exposing children to superhero media, even with prosocial behavioral intentions, resulted in increased physical and relational aggression.…”
Section: Introductionmentioning
confidence: 99%